Linking the performance of entrepreneurial universities to technoparks and university characteristics in Turkey - Tüzin Baycan Levent; Gökçen Arkali Olcay (REGION, 2021)
Universities' third mission of knowledge commercialization imposes them a core role as being entrepreneurial universities in the triple helix along with the government and industry to contribute to the regional development and innovation. The emergence of entrepreneurial universities is relatively a new concept in Turkey attracting stakeholders of higher education, policy developers and scholars. The contribution of the entrepreneurial universities to the entrepreneurship ecosystem and regional innovativeness has been quantified via an index developed by the Turkish Scientific and Technological Research Council starting in 2012. Using this index as the dependent variable in our model, we explore how being located in a technology development zone and other university-specific characteristics play a role in getting higher scores in this index of the most entrepreneurial and innovative universities. Our analyses highlight how the contribution of universities undertaking technology development activities through a formal channel as in the form of technology development zones differ to the regional entrepreneurship and innovativeness. While the performance of the technology development zone and the composition of the university students with higher ratios of graduate students positively improve the scores of the universities, universities that are smaller in sizes are found to have higher scores.
Keywords: 330; Entrepreneurial universities in Turkey; technoparks; knowledge commercialization; geographical proximity; regional innovation